My little pony, friendship is magic triple feature. [videorecording (DVD)] Pinkie Pie party, Princess Twilight sparkle, Royal pony wedding - Ward, Brian (Producer) (Shout! Factory Kids, 2026)
The studious Twilight Sparkle may have learned the true meaning and value of friendship through the amazing bonds she's formed with every pony in Ponyville, but the lessons keep on coming! Join Twilight Sparkle and her friends Rainbow Dash, Fluttershy, Apple Jack, Pinkie Pie, Rarity and little Spike as they embark on one crazy adventure after another, including the greatest wedding Equestria's ever seen. And you're invited!